NSZZ „Solidarność” – ruch i idee w latach 1980-1981 - Skrzyniarz, Jakub (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
The article describes the political thought of NSZZ “Solidarność”. At the beginning the article presents the creation of “Solidarność”, the most important events of 1980-1981 and the tragic events of martial law. Next, the article looks at the most important ideological sources from which the political thought of “Solidarność” was drawn. The article points to the most important assumptions of the political thought of “Solidarność” and the values that guided the movement, through the analysis of the most important ideological programs. The article also describes the attitude of “Solidarność” to socialism. Finally, the article briefly presents the ideas of Solidarność Walcząca.
Keywords: Solidarity; PRL; socialism; communism; PZPR; Lech Wałęsa; Jacek Kuroń; Adam Michnik; social solidarity; egalitarianism; democracy; the Soviet Union; Fighting Solidarity; Polish months